Monetary Policy under Behavioral Expectations: Theory and Experiment - Cars Hommes; Domenico Massaro; Matthias Weber (Tinbergen Institute, 2015)
Expectations play a crucial role in modern macroeconomic models. We replace the common assumption of rational expectations in a New Keynesian framework by the assumption that expectations are formed according to a heuristics switching model that has performed well in earlier work. We show how the economy behaves under these assumptions with a special focus on inflation volatility. Contrary to comparable models based on full rationality, the behavioral model predicts that inflation volatility can be lowered if the central bank reacts to the output gap in addition to inflation. We test the opposing theoretical predictions with a learning to forecast experiment. The experimental results support the behavioral model and the claim that reacting to the output gap in addition to inflation can indeed lower inflation volatility.
Keywords: C90; E03; E52; D84; 330; Experimental Macroeconomics; Heterogeneous Expectations; Learning to forecast Experiment; Trade-off Inflation and Output Gap